IFIP glossary of terms used in production control - Burbidge, John L. (North-Holland ; Sole distributors for the U.S.A. and Canada, Elsevier Science Pub. Co., 1987)
There is at present no universally accepted source giving definitions in English of the principal terms used in Production Control and in closely related areas. Most of the dictionaries and glossaries which do exist in this field fail to cover the full range of ideas which need to be considered during an intelligent discussion of the subject. Definitions given in different sources for Production Control terms differ not only in wording, but also in many cases in the concepts which they cover. The IFIP Glossary is intended to meet this perceived need, the immediate audience for the book being IFIP WG 5.7, the working group concerned with the automation of Production Management and other related subjects. The Glossary is organised in the following way: - The subject field was classified into sub-fields by Management function. - Each of these sub-fields was analysed to discover the main concepts with which it is concerned. - Terms were selected for each concept, using as far as possible terms which are already in common use. - Definitions were selected or written for each term. This approach of starting with subject classification is believed to be new in the field of production. Care has been taken to check the Glossary with the APICS dictionary (USA), and with British standards. Notes are included in Part 2 to explain the reasons for selecting a particular meaning for a term, in those cases where there are wide differences in the meanings chosen by different sources. Some consensus about the meaning of words is essential for communication. On the other hand, there is a danger that if the accepted framework of meanings is too rigid, if may hinder the future development of the discipline. It is hoped that a reasonable balance has been found between these conflicting influences. The Glossary should be useful not only to WG 5.7 members, but also to Engineers and Academics in all countries where a knowledge of English is important to industrial development.